Scholarly Discourse on Equity, Inclusion, and Education by Scholars in Indonesia: A Bibliometric and Science Mapping Analysis - Moosa, Visal; Rizkyanti, Charyna Ayu; Sumintono, Bambang (Muslim Education Review, 2024)
Equity, inclusion, and education are remarkable elements encompassed in the United Nations sustainable development goals (SDGs). As such, there is a growing number of publications on these topics presenting some challenges to envision an overarching understating of the connections among these subjects. Hence, the purpose of the current study is to explore the body of research that involves equity, inclusion, and education that is contributed by Indonesian academia by employing bibliometric and science mapping analysis. The search was conducted on SCOPUS database which resulted in some 400 plus documents after applying the pre-defined inclusion and exclusion criteria. Data was analyzed employing various bibliometric analysis indicators such as number of publications, contributing institutions, citation, co-citation, and keywords. Microsoft excel and VOSviewer software was employed for conducting the analysis. The findings revealed that the number of publications and citations on the topics has been quiet fluctuating. Analyses of the intellectual and conceptual structure revealed that trans-disciplinary nature of scholarship on the topic. Based on the findings, the needs for a greater emphasis on research in these areas by Indonesian institutions/researchers are realized. It is also suggested that researchers employ an integrated approach by investigating variables from the policy and practice perspectives as well as at an organizational or systemic level. The findings are string support that education is an integral component of achieving equity and inclusion which should be taken into account while devising policies and implementing the same.